PENERIMAAN AUDITOR TERHADAP UNDER-REPORTING TIME - Srimindarti, Ceacilia; Puspitasari, Elen (Proceeding Fakultas Ekonomi, 2012)
This study seeks to analyze the relationship between the factors that affect the auditors acceptance of under-reporting time. Auditorâs who worked in Public Accounting in Indonesia is an object in this study using questionnaire-based survey that was sent. The data have been collected and analyzed using SPSS. Expectancy theory and the theory of goal setting is the basic theory used to explain the behavior of auditors underreporting time in accepting. The results of this study found that locus of control variables have a positive and significant impact on acceptance of under-reporting time, while the variable of organizational commitment auditor has no influence on the acceptance of under-reporting time. Adversely affect the auditors expertise acceptance under-reporting time. These results indicate that the internal factors affecting the acceptance of individual auditorâs under-reporting time. Keywords : locus of control, auditorâs expertise, organizational commitment, acceptance of under-reporting time, expectancy theory and the theory of goal setting.